2021
DOI: 10.1111/ecog.05520
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting seasonal patterns of relative temperature and thermal heterogeneity and their influence on breeding and winter bird richness patterns across the conterminous United States

Abstract: Environmental heterogeneity enhances species richness by creating niches and providing refugia. Spatial variation in climate has a particularly strong positive correlation with richness, but is often indirectly inferred from proxy variables, such as elevation and related topographic heterogeneity indices, or derived from interpolated coarse‐grain weather station data. Our aim was to develop new remotely sensed metrics of relative temperature and thermal heterogeneity, compare them with proxy measures, and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Regions with higher vegetation coverage could offer a mixture of resources ( e.g ., sites for nesting and roosting and food resources) for mountain birds. In addition, habitats in these areas would likely provide considerable benefits in terms of biodiversity, especially for species threatened by climate change ( Heller & Zavaleta, 2009 ; Elsen et al, 2021 ). Migrant species tolerate habitat disturbances better ( Levey, 1994 ; Smith, Salgado & Robertson, 2001 ) and are more flexible than resident species in their habitat use ( Karr, 1976 ; Hutto, 1989 ; Greenberg, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Regions with higher vegetation coverage could offer a mixture of resources ( e.g ., sites for nesting and roosting and food resources) for mountain birds. In addition, habitats in these areas would likely provide considerable benefits in terms of biodiversity, especially for species threatened by climate change ( Heller & Zavaleta, 2009 ; Elsen et al, 2021 ). Migrant species tolerate habitat disturbances better ( Levey, 1994 ; Smith, Salgado & Robertson, 2001 ) and are more flexible than resident species in their habitat use ( Karr, 1976 ; Hutto, 1989 ; Greenberg, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Herrera (1978) found that the proportion of migrant passerine birds was increased with increasing latitude in Europe. Hypotheses regarding habitat complexity and land cover types have been proposed, and the importance of habitat heterogeneity has been noted ( Elsen et al, 2021 ). Most species have strong associations with one or more land cover types ( Elsen et al, 2021 ) and specific food resources ( Willson, 1976 ; Helle & Fuller, 1988 ), which can influence the bird species richness pattern.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations